(untitled) (Experimental biology, 2009)
On transplants sites and country farms researches were carried out in Almaty area. Allocation different kinds media agar to a nutrient medium after superficial sterilisation of a fabric from various parts of onions. A collection of pure cultures of the mushrooms allocated from collected on Almaty area, totaled 41 shtamm 7 versions of mushrooms from sort Fusarium. And also have described cultured signs and morphological signs of data isolates.